Cell Cycle Re-entry in the Nervous System: From Polyploidy to Neurodegeneration - Nandakumar, Shyama; Rozich, Emily; Buttitta, Laura (Frontiers in Cell and Developmental Biology, 2021)
Terminally differentiated cells of the nervous system have long been considered to be in a stable non-cycling state and are often considered to be permanently in G0. Exit from the cell cycle during development is often coincident with the differentiation of neurons, and is critical for neuronal function. But what happens in long lived postmitotic tissues that accumulate cell damage or suffer cell loss during aging? In other contexts, cells that are normally non-dividing or postmitotic can or re-enter the cell cycle and begin replicating their DNA to facilitate cellular growth in response to cell loss. This leads to a state called polyploidy, where cells contain multiple copies of the genome. A growing body of literature from several vertebrate and invertebrate model organisms has shown that polyploidy in the nervous system may be more common than previously appreciated and occurs under normal physiological conditions. Moreover, it has been found that neuronal polyploidisation can play a protective role when cells are challenged with DNA damage or oxidative stress. By contrast, work over the last two and a half decades has discovered a link between cell-cycle reentry in neurons and several neurodegenerative conditions. In this context, neuronal cell cycle re-entry is widely considered to be aberrant and deleterious to neuronal health. In this review, we highlight historical and emerging reports of polyploidy in the nervous systems of various vertebrate and invertebrate organisms. We discuss the potential functions of polyploidization in the nervous system, particularly in the context of long-lived cells and age-associated polyploidization. Finally, we attempt to reconcile the seemingly disparate associations of neuronal polyploidy with both neurodegeneration and neuroprotection.